Mayo Older Americans Normative Studies: Factor Analysis of an Expanded Neuropsychological Battery - Greenaway, Melanie C. (2008)
The Mayo Cognitive Factor Scores were derived from a “core battery” consisting of the WAIS-R, WMS-R, and Auditory Verbal Learning Test. The present study sought to clarify the factor structure of an expanded neuropsychological battery in normal elderly controls. Confirmatory factor analysis was performed on the WAIS-III, WRAT-3 Reading, Boston Naming Test, Controlled Oral Word Association Test, Category Fluency, Rey-Osterrieth Complex Figure, Visual Form Discrimination, and Trail Making Test A & B. A base four-factor model consistent with the WAIS-III factor structure was utilized. Only one novel five factor model differentiating processing and motor speed tests improved upon this base model. Other models did not, including a factor for executive function, division of construction/visuospatial ability, or “hold”/“no hold” language abilities.